Does Willful Ignorance Deflect Punishment? - An Experimental Study - Björn Bartling; Florian Engl; Roberto A. Weber (University of Zurich, Department of Economics, 2013)
This paper studies whether people can avoid punishment by remaining willfully ignorant about possible negative consequences of their actions for others. We employ a laboratory experiment, using modified dictator games in which a dictator can remain willfully ignorant about the payoff consequences of his decision for a receiver. A third party can punish the dictator after observing the dictator's decision and the resulting payoffs. On the one hand, willfully ignorant dictators are punished less if their actions lead to unfair outcomes than dictators who reveal the consequences before implementing the same outcome. On the other hand, willfully ignorant dictators are punished more than revealing dictators if their actions do not lead to unfair outcomes. We conclude that willful ignorance can circumvent blame when unfair outcomes result, but that the act of remaining willfully ignorant is itself punished, regardless of the outcome.
Keywords: C91; D63; 330; willful ignorance; third party punishment; dictator game; fairness